ANALISIS DAN MITIGASI RISIKO BENCANA GELOMBANG EKSTREM DAN ABRASI PANTAI DI PANTAI MUARO SASAK KABUPATEN PASAMAN BARAT [DISASTER RISK MITIGATION AND ANALYSIS OF EXTREME WAVES AND COASTAL ABRASION IN MUARO SASAK BEACH, WEST PASAMAN REGENCY] - Marhamah, Ithvi; Mulia, Fajar Agung; Danhas, Mardayeli; Fachrin, Rachma Deli; Silvia, Silvia; Mardyah, Suci; Rahmat, Hayatul Khairul (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
West Pasaman Regency, located in West Sumatra Province, faces a high risk of coastal disasters such as extreme waves and coastal abrasion. This study focuses on Muaro Sasak Beach, an area with increasing environmental degradation due to wave action and sedimentation. The aim of this research is to analyze spatial disaster threats and formulate mitigation strategies using risk-based assessments. The study applies a composite index model based on BNPB (2020) guidelines and Interpretative Structural Modeling (ISM) to map threats and prioritize actions. Results indicate that 50.11% of the 563.52-hectare coastal zone is at high risk. The ISM framework identifies ecosystem restoration and risk mapping as top-priority strategies, followed by structural protections and land use policies. This research provides evidence-based recommendations to support disaster management planning in coastal areas of Pasaman Barat.